Case report: Anti-neurexin-3α-associated autoimmune encephalitis secondary to contrast-induced encephalopathy - Zhu, Lin; Shang, Qunzhu; Zhao, Charlie Weige; Dai, Shujuan; Wu, Qian (Frontiers in Neurology, 2023)
A 54-year-old man complained of episodic stinging in his left eye along with weakness and numbness in his right upper and lower extremities for 1 month. The neurological examination was negative. MRI showed bilateral paraventricular demyelination. CTA showed significant stenosis of the left internal carotid (60%) and vertebral arteries (70%). He underwent left internal carotid stenting and was intubated during the procedure. After the procedure, he did not wake up from anesthesia, and he developed flexion and spasticity in the right arm immediately. Thereafter, he was sent to the neurocritical unit (NCU). Anti-seizure treatment was adopted due to recurrent general tonic-clonic seizures. Two days later (day 15 of hospitalization), brain edema and meningitis appeared in MRI, and contrast-induced encephalopathy (CIE) was mainly considered, with the support of CSF results. After 18 days (day 21 of hospitalization), serum anti-neurexin-3α IgG was detected at a dilution of 1:10. Anti-neurexin-3α-associated encephalitis was diagnosed. The patient was fully recovered 7 months after taking immunoglobulin, steroids, mortimycophenate, and cyclophosphamide. Meanwhile, anti-neurexin-3α antibody IgG was negative in both CSF and serum. MRI was also normal. Although scarce evidence clarified the relationship between CIE and anti-neurexin-3α-associated encephalitis, we inferred that the BBB damaged by CIE may result in the anti-neurexin-3α antibody entrance into the CSF from serum, which led to autoimmune encephalitis (AIE).